Nanostructured porous silicon: The winding road from photonics to cell scaffolds. A review. - Hernandez-Montelongo, Jacobo; Muñoz-Noval, Alvaro; García-Ruíz, Josefa P.; Torres-Costa, Vicente; Martin-Palma, Raul J.; Manso-Silvan, Miguel (Frontiers in Bioengineering and Biotechnology, 2015)
For over 20 years nanostructured porous silicon (nanoPS) has found a vast number of applications in the broad fields of photonics and optoelectronics, triggered by the discovery of its photoluminescent behavior in 1990. Besides, its biocompatibility, biodegradability, and bioresorbability make porous silicon (PSi) an appealing biomaterial. These properties are largely a consequence of its particular susceptibility to oxidation, leading to the formation of silicon oxide which is readily dissolved by body fluids. This paper reviews the evolution of the applications of PSi and nanoPS from photonics through biophotonics, to their use as cell scaffolds, whether as an implantable substitute biomaterial, mainly for bony and ophthalmological tissues, or as an in-vitro cell conditioning support, especially for pluripotent cells. For any of these applications, PSi/nanoPS can be used directly after synthesis from Si wafers, upon appropriate surface modification processes, or as a composite biomaterial. Unedited studies of fluorescently active PSi structures for cell culture are brought to evidence the margin for new developments.